2021
DOI: 10.1101/2021.05.10.443367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnosis and analysis of unexplained cases of childhood encephalitis in Australia using metagenomic next-generation sequencing

Abstract: Encephalitis is most often caused by a variety of infectious agents, the identity of which is commonly determined through diagnostic tests utilising cerebrospinal fluid (CSF). Immune-mediated disorders are also a differential in encephalitis cases. We investigated the clinical characteristics and potential aetiological agents of unexplained encephalitis through metagenomic next-generation sequencing of residual clinical samples of multiple tissue types and independent clinical review. A total of 43 specimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 63 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Further, there was concordant documentation of 56 different pathogens, including 30 bacterial pathogens, 19 viral pathogens, six fungi and one Balamuthia mandrillaris ( B. mandrillaris ) as the only amoeba detected in a CSF sample ( Table 1 and Figure 4 ). Of the 217 CSF samples in which mNGS investigation yielded results discordant with the routine method, mNGS conclusively found a pathogen in 38/103 CSF samples in which routine investigations found no pathogen, as reported in 25/51 studies: mNGS over-detected RNA viruses, including Human rhinovirus and Human coronavirus ( Li et al, 2021 ), Coxsackievirus 9 and Mumps virus ( Kawada et al, 2016 ), Saint-Louis Encephalitis virus ( Chiu et al, 2017 ), Powassan Virus ( Piantadosi et al, 2018 ), Toscana virus ( Tschumi et al, 2019 ), Jamestown Canyon virus ( Solomon et al, 2021 ), Enterovirus A71 ( Leon et al, 2020 ), and Hepatitis E virus ( Carbo et al, 2020 ), while only HSV-1, HHV-6, and EBV were identified as DNA viruses ( Zhang Y. et al, 2019 ; Carbo et al, 2020 ). Bacterial pathogens documented in 11% of these cases included Listeria monocytogenes in four cases ( Yao et al, 2016 ; Lan et al, 2020 ), Ureaplasma parvum in three cases ( Wang et al, 2020 ; Xing X.-W. et al, 2021 ; Zhan et al, 2021 ) and one case each was detected of Klebsiella pneumoniae ( Zeng et al, 2021 ), Pasteurella multocida ( Morsli et al, 2022 ), Enterococcus faecalis ( Zhang et al, 2021a ), Nocardia farcinica ( Zhang et al, 2021b ), Streptococcus suis ( Zhang et al, 2020 ), and Psychrobacter sp.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Further, there was concordant documentation of 56 different pathogens, including 30 bacterial pathogens, 19 viral pathogens, six fungi and one Balamuthia mandrillaris ( B. mandrillaris ) as the only amoeba detected in a CSF sample ( Table 1 and Figure 4 ). Of the 217 CSF samples in which mNGS investigation yielded results discordant with the routine method, mNGS conclusively found a pathogen in 38/103 CSF samples in which routine investigations found no pathogen, as reported in 25/51 studies: mNGS over-detected RNA viruses, including Human rhinovirus and Human coronavirus ( Li et al, 2021 ), Coxsackievirus 9 and Mumps virus ( Kawada et al, 2016 ), Saint-Louis Encephalitis virus ( Chiu et al, 2017 ), Powassan Virus ( Piantadosi et al, 2018 ), Toscana virus ( Tschumi et al, 2019 ), Jamestown Canyon virus ( Solomon et al, 2021 ), Enterovirus A71 ( Leon et al, 2020 ), and Hepatitis E virus ( Carbo et al, 2020 ), while only HSV-1, HHV-6, and EBV were identified as DNA viruses ( Zhang Y. et al, 2019 ; Carbo et al, 2020 ). Bacterial pathogens documented in 11% of these cases included Listeria monocytogenes in four cases ( Yao et al, 2016 ; Lan et al, 2020 ), Ureaplasma parvum in three cases ( Wang et al, 2020 ; Xing X.-W. et al, 2021 ; Zhan et al, 2021 ) and one case each was detected of Klebsiella pneumoniae ( Zeng et al, 2021 ), Pasteurella multocida ( Morsli et al, 2022 ), Enterococcus faecalis ( Zhang et al, 2021a ), Nocardia farcinica ( Zhang et al, 2021b ), Streptococcus suis ( Zhang et al, 2020 ), and Psychrobacter sp.…”
Section: Resultsmentioning
confidence: 58%
“…As for the geographic origin of published studies, 28 (56%) were published in Asia, including 25 (49%) from Chinese laboratories ( Table 1 ), one each from Saudi Arabia ( Guan et al, 2021 ), Bangladesh ( Saha et al, 2019 ), and Japan ( Kawada et al, 2016 ) (6.1%); nine in the United States ( Table 1 ); one in Mexico ( Joanna María et al, 2016 ); five in France (10%) (Tabel 1); two in Netherlands ( Edridge et al, 2019 ; Carbo et al, 2020 ); and one each in Switzerland, the United Kingdom, and Spain ( Tschumi et al, 2019 ; Leon et al, 2020 ; Manso et al, 2020 ). One study was also published in Guinea and another in Australia ( Eibach et al, 2019 ; Li et al, 2021 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations